ANALISIS APLIKASI PAJAK (E-FILLING DAN E-BILLING) BERBASIS TECHNOLOGY ACCEPTANCE MODEL (TAM) - Della Fadhilatunisa; M. Miftach Fakhri; Rosidah; Radhiah; Raodahtul Jannah (Universitas Islam Negeri Alauddin Makassar, 2022)
The Covid-19 pandemic affected the economy in Indonesia so the government relies on taxes as the main source of national income to continue the country's development. The purpose of the research is to find out the perspective of users, namely taxpayers, on the taxation application (e-filling and e-billing) with technology acceptance model (TAM). This research population is a lecturer in taxation courses at the Islamic University in Makassar City as a taxpayer (WP) which amounts to 96 people so that the entire population is also used as a research sample. Teknik data collection is a questionnaire through e-mail and google form. Data analysis using the Smart PLS application by testing hypotheses, namely structural models or inner models. The results of the study explain the taxpayer's opinion on the application of tax digitization that has a positive influence from the results of the analysis of the inner model with the original value of the sample that explains the positive results.